Susceptibility of Callosobruchus chinensis (Coleoptera: Bruchidae) infesting chickpea to low energy electrons - SINGH, SUBADAS; BHALLA, SHASHI; SRINIVASAN, KALYANI; PRASAD, TELAPROLU VENKATA; PRAMOD, RADHEYSHYAM; DWIVEDI, JISHNU (The Indian Journal of Agricultural Sciences, 2015)
Low energy electrons irradiation has been reported to effectively disinfest the grains and is considered safe and environment friendly. Laboratory experiments were conducted to study the effect of low energy electrons at various doses, viz. 0.25, 0.5, 0.75, 1.0, 1.25 and 1.5 kGy at an energy level of 500 keV on different stages of adzuki bean weevil, Callosobruchus chinensis (L.) infesting chickpea. Percent adult emergence from seeds infested with pupa decreased from 76.6 % in the control (unirradiated) to 6% at irradiation dose of 1.5 kGy. There was no adult emergence from the eggs oviposited by irradiated female at 0.25 kGy, whereas, untreated female produced 95.3% of adults in next generation. Egg stage was comparatively more sensitive while late larva was most tolerant stage to the treatment. The LD99 values of egg, early larva, mid larva, late larva and pupa were 1.21, 1.25, 2.94, 3.64, and 1.81 kGy respectively. The estimated doses for 50 and 99% control of adults were 1.09 and 2.25 kGy respectively. Low energy electron treatment did not affect the germination of chickpea seeds.